(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
This contribution intends to probe, in the context of generative grammar, the types of mandatory control in the final adverbial infinitive constructs in the Italian language. Based on the analysis carried out on examples taken from the Coris corpus as well as those taken from the Italian electronic and paper media, we can conclude that the mandatory control in the final adverbial infinitive constructs can be complete, partial or divided. In the cases of complete and divided control the semantic and morphological value of the silent subject (PRO) is identical. In the contexts of partial control semantically PRO is always in the plural while morphologically it can be in the singular when its partial controller is in the singular.